Pengaruh Kualitas Produk, Harga, dan Iklan terhadap Keputusan Pembelian Produk Lipstik Emina di Yogyakarta - Ayu Yunefa; Sri Ekanti Sabardini (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2020)
The increase in sales in the cosmetics industry, especially in the youth segment, is interesting to study more deeply, and has not been revealed much. Studies on the effect of the marketing mix on purchasing decisions have often been carried out, however, there are still not many teenagers making decisions about purchasing teen cosmetics. There are still some differences in research results, especially regarding the factors that affect purchasing decisions. This research was conducted on Emina’s teenage cosmetics consumers, especially on lipstick products. Want to know the price, product quality and advertisements affect the purchase decision of Emina lipstick products. A survey was conducted through distributing forms via google form, using purposive sampling method, to 110 consumers of Emina’s lipstick, who bought their own products for their own use. The results showed that only advertising had an effect on purchasing decisions, while product quality and price were partially insignificant with purchasing decisions. Simultaneously, the three independent variables have an effect on purchasing decisions. The results of this study provide input to Emina Cosmetics, especially Lipstick products, to continue to improve and improve their advertisements, because advertising is the most attractive to teenagers in product purchasing decisions.